Managing inflation and supply chain disruptions in the global economy - Akkucuk, Ulas, 1975- (Advances in logistics, operations, and management science (ALOMS) book series., 2023)
"This book deals scientifically with this post pandemic phenomenon of rising prices and supply chain disruptions that are expected to become a permanent issue that will affect all countries, and highlights way for the business community to deal with it"--